Appointment scheduling of inpatients and outpatients in a multistage integrated surgical suite: Application to a Tunisian ophthalmology surgery department. Issue 1 (2nd January 2018) - Chabouh, Safa; Hammami, Sondes; Marcon, Eric; Bouchriha, Hanen
Abstract: This article addresses the challenges of appointment scheduling of inpatients and outpatients with stochastic service times in a multistage integrated surgical suite. It takes into account the availability and compatibility of resources, with the presence of a variety of patient types. Twelve appointment heuristics are proposed and evaluated by means of a discrete event simulation model, in terms of expected patient waiting time and expected surgical suite completion time. These heuristics are further compared with a lower bound obtained by a mixed integer program. The computational experiments are based on real data of a hospital-integrated facility within an ophthalmology surgery department in a Tunisian hospital.